The reality of practicing active learning by science teachers in Madinah - Al- Subiee, Khulood Abdullah; Al Mutrafi, Rashdan bin Humaid (Journal of Educational and Psychological Sciences, 2019)
The aim of this research is to uncover the reality of the practice of science teachers in Medina for active learning, the researcher used a note card consisting of 21 phrases divided into two axes: the axis of introducing students to the objectives of the lesson, and the axis of lesson executing skill.The tool was applied after verifying its reliability and consistency. Where the research was applied to the intentional sample consisted of (10) teachers who teach science in the second semester of the academic year 1439/ 1440 H, 2018/2019 AD.The research found that: The science teacher did practice the skill of introducing students to the objectives of the lesson to a small degree of an average of (0.80), and that the science teacher was practicing the skill of implementing the lesson to a small degree of an average of (1.44). Finally, the reality of the practice of science teachers in Medina for active learning got an average of (1.25), which was a small degree. In light of the results, a number of recommendations and suggestions were made to activate the practice of science teachers for active learning.
Keywords: Science subject; science teachers; practice; active learning; intermediate stage; Medina